Status program pembelajaran di kalangan saudara baru: satu kajian kes di negeri Melaka - Mat Sah, Mohd Azmi; Ismail, Maimunah (Universiti Putra Malaysia Press, 2003)
The study aimed to identify the perception of respondents on the status of learning program that they have undergone. The study involved 60 Muslim converts and three officers of an Islamic institution. Results showed that the majority of respondents were of Chinese with Buddhism as the original religion, converted to Islam at the average age of 25.8 years, and their present age was at an average of 45.2 years. A total of 76% of respondents were women. As a whole the respondents perceived that the learning program was satisfactory. However, some areas need to be looked into seriously such as the situations in the class, the capability of teachers in using multiple languages in teaching, and several aspects of learning contents. Three problems related to learning program for the converts were identified, namely, the perception of respondents that Balai Islam is the only place to refer to when problems arise, employment status of officers and the inadequacy of curriculum.